Concepts of comorbidities, multiple morbidities, complications, and their clinical epidemiologic analogs - Ording AG; Sørensen HT (Clinical Epidemiology, 2013)
Anne Gulbech Ording, Henrik Toft Sørensen Department of Clinical Epidemiology, Aarhus University Hospital, Denmark Abstract: The proportion of older people in the world population is expected to increase rapidly during the upcoming decades. Consequently, the number of patients with multimorbidity will increase dramatically. In epidemiologic research, the concepts of multimorbidity, comorbidity, and complications have been confusing, and some of these concepts are used interchangeably. In this commentary, the authors propose a clear terminology for clinical concepts describing different aspects of multimorbidity and elucidate the relationship between these clinical concepts and their epidemiologic analogs. Depending on whether a study uses causal or predictive models, a proper distinction between concepts of multimorbidity is important. It can be very difficult to separate complications of the index disease under study from comorbidity. In this context, use of comorbidity indices as confounding scores should be done with caution. Other methodologic issues are type, duration, severity, and number of comorbidities included in the ascertainment methods, as well as sources included in the research. Studies that recognize these challenges have the potential to yield valid estimates of the comorbidity burden and results that can be compared with other studies. Keywords: epidemiology, epidemiologic methods, comorbidity, complications, diagnosis-related groups, risk adjustment